When love speaks - Attenborough, Richard; Branagh, Kenneth; Fiennes, Ralph; Rickman, Alan (EMI Records, 2001)
A selection of William Shakespeare's much-loved sonnets, read by some of the world's finest actors, together with musical settings of passages from his sonetts and plays. [Booklet]